International judicial competence in consumer actions against air companies. Commentary to the authors of the Court of Commercial of Madrid of 25/9/2018, 4/10/2018, 9/10/2018, 18/10/2018 and the judgment of the Provincial Hearing of Girona on 27/9/2018 - Ortega Giménez, Alfonso (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The regulation regarding passenger passenger rights in air transport aims to ensure that consumers are fully compensated for the damages they may suffer in the development of their flight, and that the passenger can assert their rights against the carrier or operator air in case of cancellation, denied boarding or significant flight delay. This right of compensation raises relevant issues of international judicial competence when determining the courts before which the passenger must go to effectively exercise their right. In a sector such as passenger air transport, it is usual to include clauses for the selection of courts within the conditions and terms of transport imposed by the operator and whose effectiveness will have to be evaluated in the light of private international private law.
Keywords: international air transport; passengers; Montreal Convention; international jurisdiction; applicable law